An Applied Research Proposal Towards Analysing and enchancement the Effectiveness Of Emergency Management Through Ship Operations - Burcu Öztürk Taç; Emre Akyüz; Metin Çelik (Journal of Transportation and Logistics, 2018)
Efforts about enhancement of emergency management for commercial vessels include training, updating of rules and technological improvements. Experienced ship accidents and emergency situations demonstrated that emergency management has not reached yet the intended level. In this study, a detailed literature review regarding emergency preparedness will be conducted. According to information that will be gained from expert opinions and literature review, simulation approach integrated with factor analyses will be offered about evaluation and improvement of emergency management effectiveness for ship management. In this study, it is aimed to contribute to evaluation of emergency preparedness level of each ship in the fleet of ship management companies.